2021
DOI: 10.1001/jamanetworkopen.2020.32053
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Racial Differences in Pharmacotherapy Efficacy for Smoking Cessation

Abstract: IMPORTANCE Understanding Black vs White differences in pharmacotherapy efficacy and the underlying reasons is critically important to reducing tobacco-related health disparities.OBJECTIVE To compare pharmacotherapy efficacy and examine variables to explain Black vs White differences in smoking abstinence. DESIGN, SETTING, AND PARTICIPANTSThis study is a secondary analysis of the Evaluating Adverse Events in a Global Smoking Cessation Study (EAGLES) double-blind, placebo-controlled, randomized clinical trial, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 93 publications
(224 reference statements)
2
36
1
Order By: Relevance
“…Therefore, we expected to observe a significant reduction in abstinence in African American smokers in the Pharmacogenetic Study. The range of standardized effect estimates we observed, from ORs (95%CI) of 0.31 (0.14-0.69) in the CPD model to 0.34 (0.15-0.74) in the uNMR model, encompass estimates from studies with a variety of designs: randomized on gender and OMB race 42 , stratified by OMB race 6 , or stratified by psychiatric diagnosis 8 .…”
Section: Omb Race and Abstinencementioning
confidence: 90%
See 4 more Smart Citations
“…Therefore, we expected to observe a significant reduction in abstinence in African American smokers in the Pharmacogenetic Study. The range of standardized effect estimates we observed, from ORs (95%CI) of 0.31 (0.14-0.69) in the CPD model to 0.34 (0.15-0.74) in the uNMR model, encompass estimates from studies with a variety of designs: randomized on gender and OMB race 42 , stratified by OMB race 6 , or stratified by psychiatric diagnosis 8 .…”
Section: Omb Race and Abstinencementioning
confidence: 90%
“…The copyright holder for this this version posted December 27, 2021. ; https://doi.org/10.1101/2021.12.24.21267950 doi: medRxiv preprint 5 Nollen et al identified cessation disparities and explanatory factors in analyses of US smokers in the randomized placebo-controlled trial called "Evaluating Adverse Events in a Global Smoking Cessation Study" (EAGLES, NCT01456936) 8,9 . EAGLES was designed to test the relative neuropsychiatric risks and efficacy of varenicline and bupropion to those of nicotine replacement therapy (NRT) and placebo; a total of N=8144 smokers (>=10 cigarettes per day, CPD) with and without psychiatric disorders were enrolled 9 .…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
See 3 more Smart Citations